Pendampingan Pelatihan Model Pembelajaran Quantum Teaching pada Tenaga Pendidik - Abdurahman, Ayi; Setiawati, Setiawati; Christine, Sri Erwini (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The quality of education depends on the quality of the learning process, for this reason an appropriate learning model is needed. This study aims to overcome the problem of low student scores caused by the lack of effectiveness of the learning methods used. As an alternative option, the quantum teaching learning model can be applied to improve student learning outcomes. The research approach applied is a quantitative experimental design using the ABCD (Audience, Behavior, Conditions, and Degree) training model. Data collection methods used include observation, communication, document study, and measurement techniques. The tools used to collect data included observation guides/checklists, interview guides, questionnaires, documentation, and tests. Data analysis was carried out by testing for normality and conducting a paired samples test. Based on the research results in the "paired samples test" output table, it was found that the value of Sig. (2-tailed) of 0.000 <0.05, so that H0 is rejected and Ha is accepted. Based on the average difference between pre-test and post-test learning outcomes, it can be concluded that the use of the quantum teaching learning model influences improving learning outcomes.